Green banana and ora-pro-nóbis mixed flours: nutritional and technological characteristics - Cândido, Hebert Teixeira [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; dos Ouros, Lucas Felipe [UNESP]; de Jesus, Paulo Ricardo Rodrigues [UNESP]; Izidoro, Maiqui [UNESP]; Molha, Nicholas Zanette [UNESP]; Domiciano, Vinícius Martins [UNESP] (FapUNIFESP (SciELO), 2022)
The constant need for innovation in the food industries to meet the demands of consumers and the growing market for gluten-free and high-protein products have driven studies of mixed flour. In this study, 'BRS Platina' banana fruits were processed to obtain Whole Green Banana Flour (WGBF) and Green Banana Pulp Flour (GBPF) as well as leaves of Ora-pro-nóbis Flour (OPNF). Mixed flours were prepared by blending banana flours (WGBF or GBPF) with increasing levels of OPNF (from 5 to 25%). Flours were analyzed for physicochemical characteristics, mineral contents, Water Absorption Index (WAI), Water Solubility Index (WSI), and color. The main component of banana flours was starch, in which GBPF has the highest content. The WGBF had a higher mineral content, and in both flours, the potassium was at a greater level. OPNF showed the highest protein and mineral contents. Independent of the type of banana flour, mixed flours were darker, and had higher WAI and considerable increases in Mg, Fe, and Zn than no mixed ones. The blend of banana flours and Ora-pro-nóbis leaf flour can be a viable combination for preparing a variety of food products, due to its nutritional and technological properties.
Farinhas mistas de banana verde e ora-pro-nóbis: características nutricionais e tecnológicas
Keywords: Gluten-free; Minerals; Musa spp; Pereskia aculeata; Protein; Starch